Direct visualization endoscopic retrograde appendicitis therapy versus laparoscopic appendectomy for management of acute uncomplicated appendicitis - Pan, Jun-yu; Zhi, Hui-xin; Chen, Jie-li; Chen, Hao-xin; Li, De-feng; Yao, Jun; Wang, Li-sheng (Endoscopy International Open, 2025)
Direct visualization endoscopic retrograde appendicitis therapy (ERAT), an advanced technique building upon conventional ERAT, represents a novel endoscopic approach for managing acute uncomplicated appendicitis. This study aimed to assess clinical efficacy and safety of employing cholangioscope-guided endoscopic intervention as a therapeutic approach.A retrospective analysis was conducted on 656 patients presenting with suspected acute appendicitis between February 2024 and November 2024. To minimize baseline differences, propensity score matching was applied, resulting in a final study population of 34 patients undergoing direct visualization ERAT and 68 patients treated with laparoscopic appendectomy (LA). Key outcome measures included technical and clinical success rates, operative time, time to postoperative pain resolution, length of hospital stay, recurrence rate, incidence of adverse events (AEs), and overall patient satisfaction.The technical success rate was 97.06% (33/34) in the ERAT group and 100% in the LA group (P = 0.333), while clinical success was achieved in 94.12% (32/34) of ERAT cases compared with 100% in the LA cohort (P = 0.109). Notably, ERAT was associated with a significantly shorter operative time (37 vs 50 minutes; P < 0.001) and more rapid postoperative pain relief (P = 0.001), with a greater proportion of patients reporting complete symptom resolution within 2 days of the procedure. There were no significant differences between the two groups in terms of AEs, length of hospital stay, or patient satisfaction. During follow-up, a recurrence of appendicitis was observed in one ERAT patient (2.94%, 1/34).Direct visualization ERAT demonstrated high feasibility and effectiveness as a diagnostic and therapeutic modality for acute uncomplicated appendicitis, offering a promising alternative to conventional approaches.
Keywords: Endoscopy Lower GI Tract; Stenting; Pancreatobiliary (ERCP/PTCD); Cholangioscopy